Early Improvement in Clinical Status Following Ventricular Assist Device Implantation in Children: A Marker for Survival. Issue 1 (7th April 2021) - Conway, Jennifer; Ravekes, William; McConnell, Patrick; Cantor, Ryan S.; Koehl, Devin; Sun, Benjamin; Daly, Richard C.; Hsu, Daphne T.
Abstract : Supplemental Digital Content is available in the text. Abstract : While clinical status at the time of ventricular assist device (VAD) implant can negatively affect outcomes, it is unclear if early improvement after implant can have a positive effect. Therefore, the objectives of this study were to describe the clinical status of pediatric patients supported with a VAD and determine the impact of clinical status on the 1-month follow-up form on survival and ability to discharge. This was a retrospective analysis of data collected prospectively by the Pediatric Interagency Registry for Mechanical Circulatory Support Registry (Pedimacs) Registry. The Pedimacs database was queried for patients implanted between September 19, 2012, and September 30, 2019, who were alive on VAD support at 1-month postimplant on either a paracorporeal pulsatile or intracorporeal continuous device. Four factors on the 1-month follow-up were the focus of this study: mechanical ventilation, supplemental nutritional support, inotropic support, and ambulatory status. These factors were regarded as present if detected between 1-week and 1-month postimplant and were analyzed to determine their impact on survival following 1 month of VAD support and on successful discharge from hospital in patients with implantable continuous-flow devices. The eligible study cohort consisted of 414 patients with a mean age of 9.6 ± 6.2 years, weight of 40.8 ± 32.3 kg with the majority being male (56.7%) and having cardiomyopathy (68%). An isolated left ventricular assist device (LVAD) was the most common implant (85.5%). At implant, 40% were ventilated, 57% required nutritional support, 93% were on inotropes, and 58% were nonambulating. On the 1-month postimplant form, there were significant improvements in all four categories (14% ventilator support, 46% nutritional support, 53% on inotropes, and 25% nonambulating). However, there was no significant early change in the percentage of patients requiring supplemental nutrition in the paracorporeal pulsatile devices (88% vs. 82%; p = 0.2). Presence of these clinical parameters in early follow-up postimplant had a significant negative impact on survival and on the ability of patients with continuous-flow devices to be discharged. Presence of four specific clinical parameters early after VAD placement is associated with worse overall survival and an inability to discharge patients on VAD support. Ongoing work is needed for optimization of patients before implant and aggressive rehabilitation after implant to help improve long-term outcomes.